Síntese de filamentos de carbono funcionalizados via reação de desidrogenação do etilbenzeno para utilização como sensor - Soares, Carla Caroline Sousa (2021)
The dehydrogenation of ethylbenzene is a reaction of great academic and industrial relevance. In this reaction, styrene is produced, which is an important raw material, as it has several applicability, for example, in the manufacture of plastic products. However, these catalysts, used in this type of reaction, produce deposits of carbon filaments, also called coke. Coke is all the secondary product retained in the catalysts, responsible for its deactivation. Thus, an alternative is to promote a functionality to the coke generated, giving it a purpose that can be used as a sensor for gases. Therefore, the sensitivity of this coke, for use in sensors, can be further improved through the functionalization or addition of another element (metal) in its composition. For this purpose, carbon filaments were prepared via ethylbenzene dehydrogenation reaction. Purification was performed with hydrofluoric and hydrochloric acid solutions, followed by functionalization using nitric acid. The samples were characterized using DRX, FRX, FTIR, SEM, TGA/DTA, TPR, TPO and Raman spectroscopy. The sensor response tests were performed using the probe molecules of pyridine, 1,2-dichlorobenzene and methanol at different temperatures and checking the current variation as a function of time. For tests with the pyridine molecule using the sample after functionalization with HNO3, the interaction that occurs is strong, as there was only a small fraction of desorption, showing that the material possibly reacted with pyridine. However, the test performed with the sample after treatment with H3BO3, performed at a lower temperature (30 °C), shows a small increase in electrical current after the removal of pyridine, which may suggest the existence of acidic sites in this material, in the which pyridine adsorbs but does not desorb. However, for the 1,2-dichlorobenzene analyte there was no detectable current variation signal. For the methanol probe molecule, the results of the tests on the sensor proved to be promising to identify the referent analyte.